2007
DOI: 10.1021/bi701496z
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Characterization of Full-Length Human Heme Oxygenase-1:  The Presence of Intact Membrane-Binding Region Leads to Increased Binding Affinity for NADPH Cytochrome P450 Reductase

Abstract: Heme oxygenase (HO) is the chief regulatory enzyme in the oxidative degradation of heme to biliverdin. In the process of heme degradation, this NADPH and cytochrome P450 reductase (CPR)-dependent oxidation of heme also releases free iron and carbon monoxide. Much of the recent research involving heme oxygenase is done using a 30-kDa soluble form of the enzyme, which lacks the membrane binding region (C-terminal 23 amino acids). The goal of this study was to express and purify a full-length human HO-1 (hHO-1) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 39 publications
6
52
0
Order By: Relevance
“…The membrane-binding region of full-length HO-1 has a significant influence on the kinetic characteristics of the enzyme (Huber and Backes, 2007). These differences call into question whether conditions that are adequate for measuring the activity of soluble HO-1 can be used to examine the full-length form of the enzyme.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The membrane-binding region of full-length HO-1 has a significant influence on the kinetic characteristics of the enzyme (Huber and Backes, 2007). These differences call into question whether conditions that are adequate for measuring the activity of soluble HO-1 can be used to examine the full-length form of the enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…HO-1 activity was examined using the compound bilirubin assay as previously reported (Maines, 1996;Huber and Backes, 2007) with minor modifications. Bilirubin formation was monitored at 464 to 530 nm, and the enzyme activity was calculated using the extinction coefficient 40 mM Ϫ1 cm…”
Section: Methodsmentioning
confidence: 99%
“…However, the recent characterization of a recombinant full-length HO-1 had indicated that the fulllength form exhibits a 2-to 3-fold greater activity relative to that of the truncated, soluble form, which was increased even further in the presence of lipid. Moreover, the C-terminal hydrophobic tail has an essential role with respect to membrane incorporation as well as in formation of a high-affinity complex with cytochrome P450 reductase, deemed essential for maximal catalytic activity [93][94][95]. The C-terminal domain is also the major point of sequence divergence between the two isozymes, especially in the presence of the HRMs in HO-2 [58].…”
Section: Looking Forwardmentioning
confidence: 99%
“…One reason for this is the fact that the full-length HO-1 is very unstable and susceptible to truncation that generates an inactive, soluble form (28 kDa). The C-terminal part of the protein that is cleaved causes the HO-1 to interact with membrane lipids, and its removal alters the manner by which the enzyme interacts with potential membrane binding partners (Huber, III et al, 2009;Huber, III and Backes, 2007). Most in vitro studies of HO-1 have expressed and purified a modified, but active, 30 kDa form of the enzyme that lacks the C-terminal membrane-binding sequence and is soluble as a result.…”
Section: Regulation Of Important Enzymes By Ho-1mentioning
confidence: 99%
“…Most in vitro studies of HO-1 have expressed and purified a modified, but active, 30 kDa form of the enzyme that lacks the C-terminal membrane-binding sequence and is soluble as a result. Our lab has recently modified the amino acid sequence of full-length HO-1 to remove a thrombin cleavage site in the C-terminal tale of HO-1 (Huber, III and Backes, 2007). This mutant is full-length and binds to lipid vesicles.…”
Section: Regulation Of Important Enzymes By Ho-1mentioning
confidence: 99%